Incorporating community-engaged research into a statewide community health worker-driven infrastructure for addressing health disparities in public health emergency - Azeez B. Aina; Antoniette Holt; Ashley H. Meredith; Carey Frazier; Carla Harrison; Celeste Fonseca-Tames; Fransesca Lynnet; Jasmine D. Gonzalvo; Karina Buenavides; Kourtney A.D. Byrd; Lance Boozer; Latrice Ligon; et al. (BMC Health Services Research)
Abstract Background Emergency response plans in unprecedented public health events prioritize community-based interventions for addressing health disparities. Due to their close connections and shared values with community members, positioning community health workers (CHWs) as leaders is a promising strategy for addressing health disparities. Hence, prominent public health institutions in Indiana co-developed a CHW-driven statewide infrastructure, the “Indiana Health Equity Council Community Health Worker Model” (Model) to serve as a practical framework for building a resilient and responsive public health system that strengthens the community health workforce and addresses health disparities. Objective The objective of this study was to leverage the statewide CHW Model to generate evidence for community-centered interventions addressing health disparities across state's public health preparedness districts. Methods A qualitative study was conducted among CHWs and CHW-affiliated organization representatives across 9 districts in Indiana. Data collection consisted of demographic surveys and audio-recorded focus groups facilitated by trained district CHWs. Verbatim transcripts of focus group recordings were coded by researchers using deductive approaches, and district-level focus group summaries were produced identifying emergent themes and proposed interventions. To assess the accuracy of findings, member checking was conducted with focus group participants. The proposed ideas to address health disparities were mapped to the Healthy People 2030 domains on Social Determinants of Health. Result A total of 54 individuals participated in 14 focus group sessions across nine districts. Most study participants were female (n = 49, 90.7%) and non-Hispanic (n = 46, 85.2%). A high proportion worked in community-based organizations (n = 22, 41.5%) and performed CHW roles (n = 37, 69.8%). Proposed interventions for mitigating health disparities spanned health literacy programs, enculturation of communication resources, transportation services, community needs assessments, preventative health and psychosocial programs. Fifteen proposed interventions were mapped to the social and community context domain of Healthy people 2030 framework; eight aligned with healthcare access quality and two with neighborhood and built environment. Conclusions Study findings demonstrate that leveraging the statewide Model positions CHWs to lead district efforts and generate evidence for interventions addressing health disparities across state Public Health Preparedness Districts. Future studies should assess the effectiveness of the statewide CHW Model and explore its policy implications.